1962
DOI: 10.1177/00220345620410030901
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Dental Caries Activity and the Fluoride Level and Lactobacillus Count in Saliva

Abstract: The role of salivary lactobacilli in predicting the development of dental caries has aroused much interest. A positive correlation between lactobacillus count and caries activity has been reported by a number of authors.'-10 However, some investigators found no correlation."-'4 Studies have also been made on the relationship of the fluoride content of drinking water and saliva to the salivary lactobacillus count and to the dental caries rate. Dean, Jay, Arnold, and Elvove'5 found the salivary lactobacillus cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1964
1964
1977
1977

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…When the saliva is cleared of cellular debris and mucus by centrifugation, the fluoride concentration also decreases (YAO & GRON 1970). N o correlation could be drawn in earlier investigations between the fluoride concentration in saliva and the amount of lactobacilli, the caries activity, the solubility of the enamel, the fluoride concentration in the superficial enamel layer or the number of carious teeth (MARTIN & H I L L 1950, GEDALIA, ROSENZWEIC & SADEH 1961, BUTTNER & MUHLER 1962, DVIR, GEDALIA & SULITZEANU 1962, GEDALIA, YARDENI 8c GERSHON 1963; but in these studies, which were done before the advent of the fluoride electrode, the fluoride concentrations registered were remarkably high, ranging from 0.04 to 0.46 parts/106. The calcium concentration in the saliva has also been observed to be quite stable with respect to changes in the rate of secretion; and though the secretion rate in the group studied did increase under stimulation sevenor eightfold, the concentration of calcium decreased by only less than a quarter of the corresponding content in unstimulated saliva (LUOMA 1964).…”
mentioning
confidence: 97%
“…When the saliva is cleared of cellular debris and mucus by centrifugation, the fluoride concentration also decreases (YAO & GRON 1970). N o correlation could be drawn in earlier investigations between the fluoride concentration in saliva and the amount of lactobacilli, the caries activity, the solubility of the enamel, the fluoride concentration in the superficial enamel layer or the number of carious teeth (MARTIN & H I L L 1950, GEDALIA, ROSENZWEIC & SADEH 1961, BUTTNER & MUHLER 1962, DVIR, GEDALIA & SULITZEANU 1962, GEDALIA, YARDENI 8c GERSHON 1963; but in these studies, which were done before the advent of the fluoride electrode, the fluoride concentrations registered were remarkably high, ranging from 0.04 to 0.46 parts/106. The calcium concentration in the saliva has also been observed to be quite stable with respect to changes in the rate of secretion; and though the secretion rate in the group studied did increase under stimulation sevenor eightfold, the concentration of calcium decreased by only less than a quarter of the corresponding content in unstimulated saliva (LUOMA 1964).…”
mentioning
confidence: 97%
“…Whole saliva fluoride studies conducted between 1940 and 1963 reported concen trations of more than 0.40 ppm, with a 10-fold variation in means between the studies [Cox, 1940;McClure, 1941;Martin and Hill, 1950;Gedalia et al, 1962Gedalia et al, , 1963Dvir et al, 1962]. Additional studies with animals during this early period [Wills, 1940] found plasma F level to exceed that in submaxillary saliva by a factor of about 10, this sug gesting the requirement for a mechanism more complicated than passive diffusion to explain the relationship.…”
mentioning
confidence: 98%